Comparison of cancer stem cell enrichment between spheroids derived from single-cell and multicellular aggregate cultures - Omar, Nafiis Hairuddin; Badrul, Hisham Yahaya; Mohamad Johari, Ibahim; Abhi, Veerakumarasivam *; Chan, Soon Choy; Musalmah, Mazlan; Nurhidaya, Ab. Rahim; Syarifah Masyitah, Habib Dzulkarnain; Siti Farizan, Mansor (Biomedpress, 2023)
Introduction: Cancer stem cells (CSCs) represent a distinct group of cells within cancerous tissue that possess the ability to initiate tumorigenesis and exhibit potency, self-renewal, and drug resistance. The study of CSCs often encounters challenges in obtaining these cells of interest or generating a sufficient quantity for downstream analysis. Nevertheless, it is feasible to enrich CSCs in vitro by subjecting them to conditions that stimulate their CSC properties, such as prolonged exposure to drugs or radiation, or by promoting their self-renewal capability through spheroid culture. Spheroids are a specific type of cell culture that organizes cells into a three-dimensional structure, closely mimicking the in vivo environment. These spheroids consist of a heterogeneous cell population, including CSCs or tumor-propagating cells responsible for tumor growth and maintenance. In our study, we cultured spheroids derived from single cells as well as multicellular aggregates to enrich CSCs based on their self-renewal capability and the structural organization provided by the three-dimensional context.